“Se tem batimento, tem vida”: vivências em torno da hospitalização na visão de familiares de pacientes internados no CTI - REIS, Ewerton Beckman dos (2019)
The research focuses on the experience of relatives of patients hospitalized at the Intensive Care Center. In the research, the following guiding question was established: what are the experiences of relatives of patients hospitalized at the Intensive Care Center (ICU) during their stay as a companion? The research aims to: Inform the experiences of family members during their stay as a companion of a patient admitted to the Intensive Care Center and analyze their implications for nursing. The work carried out is descriptive, with a qualitative approach. The data collection was done by interview using a semi-structured script containing open questions and a socioeconomic questionnaire. the sample consisted of 20 relatives of patients admitted to the ICU of the João de Barros Barreto University Hospital, in Belém do Pará. The thematic content analysis was chosen as the basis for the elaboration of the units. Thus, from the meanings emerged three categories for the study: Understanding CTI and emotional repercussions for family members; The family nucleus during hospitalization and The importance of the communication of the multiprofessional team with the relatives. Within the proposed, the research sought to report the experiences of family members in their stay in the CTI. The CTI still suffers from the stigma of being a place of death and little chance of exit. The family in this process faces a great obstacle in overcoming this moment and counts on the communication of the multiprofessional team to fulfill this objective. In this scenario, bringing the family member to the care is of fundamental importance for a humanized care. Understanding the wishes of the companion in a singular way and as a family component is to establish a professional attitude aiming at the integrality of the service.